Strong glacial-interglacial variability in upper ocean hydrodynamics, biogeochemistry, and productivity in the southern Indian Ocean - Tangunan, Deborah N.; Berke, Melissa A.; Cartagena-Sierra, Alejandra; Flores, José Abel; Gruetzner, Jens; Jiménez-Espejo, Francisco; LeVay, Leah J.; Baumann, Karl-Heinz; Romero, Oscar; Saavedra-Pellitero, Mariem; Coenen, Jason J.; Starr, Aidan; et al. (Communications earth & environment, 2021)
In the southern Indian Ocean, the position of the subtropical front - the boundary between colder, fresher waters to the south and warmer, saltier waters to the north - has a strong influence on the upper ocean hydrodynamics and biogeochemistry. Here we analyse a sedimentary record from the Agulhas Plateau, located close to the modern position of the subtropical front and use alkenones and coccolith assemblages to reconstruct oceanographic conditions over the past 300,000 years. We identify a strong glacial-interglacial variability in sea surface temperature and productivity associated with subtropical front migration over the Agulhas Plateau, as well as shorter-term high frequency variability aligned with variations in high latitude insolation. Alkenone and coccolith abundances, in combination with diatom and organic carbon records indicate high glacial export productivity. We conclude that the biological pump was more efficient and strengthened during glacial periods, which could partly account for the reported reduction in atmospheric carbon dioxide concentrations.